Association between vitamin D status and malondialdehyde in T2DM patients with painful diabetic peripheral neuropathy: Vitamin D and MDA in painful diabetic peripheral neuropathy - Hassan, Alan Bapeer; Ahmed Al-Dosky, Ali Hussein (Cellular and Molecular Biology, 2023)
The association of vitamin D with oxidative stress in type 2 diabetes mellitus (T2DM) patients with peripheral neuropathy (pDPN) has not been investigated in the literature yet. In this regard, we aimed to investigate the link between vitamin D status and malondialdehyde secretion in T2DM with pDPN. We included the T2DM patients with and without pDPN from a main tertiary medical diabetic center in Duhok City in this case-control investigation from September 2021 to March 2022. The patients aged between 40 and 70 years old. The patients were diagnosed based on the American Diabetes Association criteria. The T2DM patients with pDPN had a significantly lower level of vitamin D (12.10 ng/ml vs. 16.86 ng/ml; P=0.0013.) compared to the patients without compilations, respectively. The T2DM patients with pDPN had a significantly higher prevalence of severe deficiency (45.83% vs. 16.67%), while the patients without compilations had a significantly higher prevalence of deficient vitamin D (50.0% vs. 37.50%; P=0.0053). Moreover, the T2DM patients with pDPN had a significantly higher concentration of MDA compared to the T2DM patients without complications (30.55 nmol/ml vs. 16.6 nmol/ml; P=0.0098). The study did not find a significant correlation between MDA and vitamin D levels in T2DM patients with pDPN. This study showed that a higher concentration of MDA was not associated with lower vitamin D levels in T2DM patients with pDPN.